Methane capture and nitrogen purification from a nitrogen rich reservoir by pressure swing adsorption; experimental and simulation study. Issue 5 (October 2021) - Karimi, Kian; Fatemi, Shohreh
Abstract: Simultaneous nitrogen purification and methane capturing, from a nitrogen-rich methane reservoir, in one process was studied by design and simulation of the pressure swing adsorption (PSA) as an economic process rather than the cryogenic one. The required adsorption model parameters; adsorbent isotherms and mass transfer resistances of the species were predicted by the experimental studies. The results of the dynamic adsorption model were validated by comparison of the CH4 -N2 breakthrough curves from the adsorption step of a lab-scale PSA process, with 6.7% absolute average relative deviation (AARD). Ultimately, the design and simulation were developed to the pilot scale and the operating conditions were optimized by statistical approach to enrich methane and purify nitrogen, simultaneously, and to be able to use each stream in commercial applications. It was resulted that at optimal operating conditions, from a reservoir with 20 bar pressure, containing 20 mol% CH4, at the cyclic steady PSA, nitrogen stream would purify up to 95 mol% with 63% recovery and, at the same time, methane would enrich up to 40% with 83% recovery. Therefore this process offers environmental motivation and development for production of high-pressure nitrogen as well as enriched methane product with its application in lean gas turbines from the low methane content gas reservoirs. Graphical Abstract: ga1 Highlights: Saving energy for purification of N2 and CH4 capturing from N2 (rich)-CH4 reservoir, by PSA. High pressure N2 production without need of feed compression costs, by PSA. Doubled CH4 fraction stream from regeneration section by a dual-bed PSA process. The recovered CH4 stream would be used for lean gas turbines and burners.